Improving Science Learning Outcomes in Theme 5 Subtema 1 Learning Through The Discovery Learning Model for 5th Class Students of SDN 1 Baturetno - Elyas Janu Estiyanto (Universitas Sebelas Maret, 2020)
This study aims to improve science learning outcomes using the discovery learning model in fifth grade students of SD Negeri I Baturetno for the 2020/2021 academic year. This type of research is collaborative classroom action research. The subjects in this study were fifth grade students of SD Negeri I Baturetno with a total of 14 students consisting of 9 male students and 6 female students. The method of collecting data is through observation and tests. The data analysis technique was carried out qualitatively and quantitatively. The results showed that in the first cycle student learning outcomes only reached 50% to 86% in the second cycle, meaning that there was an increase in the percentage of completeness about 36% in the second cycle. From the discussion above, it can be said that there is an increase in students' science learning outcomes during classroom action research. The action in this study was stopped and said to be successful in cycle II because it had reached the success criteria.